A Modified Beagle Model of Inducible Atrial Fibrillation Using a Right Atrium Pacemaker - Yang,Song (2020)
Abstract Objective: To modify the chronic atrial fibrillation of atrial tachycardia pacing in beagles with a homemade pacemaker placed outside the body and to evaluate connective tissue growth factor and fibrosis of atrial tissue in our modified atrial tachycardia pacing beagle model. Methods: Twelve adult beagles of either sex were randomly divided into an atrial tachycardia pacing group and a control group (n=6 in each group). We performed the temporary pacemaker implantation at the right atrial appendage and put the pacemaker into the pocket of dog clothing in the atrial tachycardia pacing group. After eight weeks of atrial tachycardia pacing, the electrocardiography, transthoracic echocardiography, hematoxylin-eosin staining, and Masson’s staining of the right atrial appendages were performed along with the immunohistochemistry, quantitative real-time polymerase chain reaction, and Western blot analysis of connective tissue growth factor, collagen I, and collagen III. Results: In the atrial tachycardia pacing group, atrial fibrillation was induced in five beagles (83.3%); the left atrium enlarged significantly; more canines had mitral regurgitation; and the Masson’s staining, quantitative real-time polymerase chain reaction, and Western blot results demonstrated more obvious fibrosis of the left atrium. Conclusion: The modified beagle model of atrial fibrillation using a right atrium pacemaker outside the body was effective, increased connective tissue growth factor and collagen I messenger ribonucleic acid overexpression, and induced atrial fibrosis.